Policies/politics, heritages and arts in contemporary cities - Gonçalves, R. S.; Infantino, J.; Raposo, O. (18th IUAES World Congress abstracts book, 2018)
This panel aims to investigate knowledge, arts and policies in urban circuits through a transnational perspective. Our focus is on cultural production and performances by social collectives that employ political, cultural, management, economic and labor resources engendering exhibition scenarios, visibilities and disputes on urban public spaces. This comparative and ethnographic perspective (in its various forms) intends to contribute with an understanding on contemporary uses of public spaces in the city, in order to debate (re) urbanization processes and the role cultural practices, festive and artistic performances play in this context. We also propose a reflexive discussion on anthropologist’s practices and contemporary public policies, especially those with a cultural and heritage focus. This panel proposal is based on cooperation projects between researchers from Brazil, Argentina and Portugal with a vast experience in cultural and artistic practices research in the cities of Rio de Janeiro, Buenos Aires and Lisbon. Panel coordinators have also taken part in organizing national and international scientific events, including work groups and round tables, as well as joint bibliographic productions.